2007
DOI: 10.1177/1358863x07080630
|View full text |Cite
|
Sign up to set email alerts
|

Acute lower limb ischemia as the initial symptom of acute myeloid leukemia

Abstract: Although coagulatory system disorders are well recognized in patients with acute leukemia, these usually present with either hemorrhagic complications or thrombosis of small vessels. Large vessel thrombosis is a very rare clinical presentation. We present a patient with previously undiagnosed acute myeloid leukemia (M5), who was referred to our hospital with symptoms of acute ischemia of his right lower limb. Occlusion of the right external iliac artery due to a combination of leucostasis and coagulation disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
1
17
0
5
Order By: Relevance
“…Embolism of periphery arteries with ischemic lesion of corresponding extremities is reported in some clinical cases [4]. Priapism in male patients due to leukostasis represents a special emergency situation.…”
Section: Basic Principlesmentioning
confidence: 99%
“…Embolism of periphery arteries with ischemic lesion of corresponding extremities is reported in some clinical cases [4]. Priapism in male patients due to leukostasis represents a special emergency situation.…”
Section: Basic Principlesmentioning
confidence: 99%
“…De Stefano et al [3] reported that there were 6.3% people caught by thrombosis, 80% by venous thrombosis, and 20% by with arterial [3]. As far as we know, only nine cases of acute leukemia that presents to be acute lower limb ischemia caused by large artery occlusion have been traced in English literatures [4]. They include two cases in ALL, four cases in APL, and three cases in non-M3 AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperleukocytosis occurs in 5–13% of adult AML, especially in FAB M4 and M5 subtypes . These myeloblasts tend to be larger and less deformable , causing sluggish blood flow within the microcirculation, obstruction of microchannels, and formation of blast aggregates . There is also increased expression of adhesion molecules and endothelial cell production of cytokines that recruit additional myeloblasts, contributing to thrombus formation .…”
Section: Discussionmentioning
confidence: 99%